APOE2 Exacerbates TDP‐43 Related Toxicity in the Absence of Alzheimer Pathology. Issue 4 (10th January 2023) - Meneses, Axel D.; Koga, Shunsuke; Li, Zonghua; O'Leary, Justin; Li, Fuyao; Chen, Kai; Murakami, Aya; Qiao, Wenhui; Kurti, Aishe; Heckman, Michael G.; White, Launia; Xie, Manling; et al.
Abstract : Objective: Recent evidence supports a link between increased TDP‐43 burden and the presence of an APOE4 gene allele in Alzheimer's disease (AD); however, it is difficult to conclude the direct effect of APOE on TDP‐43 pathology due to the presence of mixed AD pathologies. The goal of this study is to address how APOE isoforms impact TDP‐43 pathology and related neurodegeneration in the absence of typical AD pathologies. Methods: We overexpressed human TDP‐43 via viral transduction in humanized APOE2, APOE3, APOE4 mice, and murine Apoe ‐knockout ( Apoe ‐KO) mice. Behavior tests were performed across ages. Animals were harvested at 11 months of age and TDP‐43 overexpression‐related neurodegeneration and gliosis were assessed. To further address the human relevance, we analyzed the association of APOE with TDP‐43 pathology in 160 postmortem brains from autopsy‐confirmed amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration with motor neuron disease (FTLD‐MND) in the Mayo Clinic Brain Bank. Results: We found that TDP‐43 overexpression induced motor function deficits, neuronal loss, and gliosis in the motor cortex, especially in APOE2 mice, with much milder or absent effects in APOE3, APOE4, or Apoe ‐KO mice. In the motor cortex of the ALS and FTLD‐MND postmortem human brains, we found that the APOE 2 allele was associated with more severe TDP‐43‐positive dystrophic neurites. Interpretation: Our data suggest a genotype‐specific effect of APOE on TDP‐43 proteinopathy and neurodegeneration in the absence of AD pathology, with the strongest association seen with APOE2 . ANN NEUROL 2023;93:830–843